2018
DOI: 10.1007/s10439-018-2043-5
|View full text |Cite
|
Sign up to set email alerts
|

Computational Pre-surgical Planning of Arterial Patch Reconstruction: Parametric Limits and In Vitro Validation

Abstract: Surgical treatment of congenital heart disease (CHD) involves complex vascular reconstructions utilizing artificial and native surgical materials. A successful surgical reconstruction achieves an optimal hemodynamic profile through the graft in spite of the complex post-operative vessel growth pattern and the altered pressure loading. This paper proposes a new in silico patient-specific pre-surgical planning framework for patch reconstruction and investigates its computational feasibility. The proposed protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Mouse iPSC-derived Acta2 hrGFP+ cell sheets had significantly higher elastic modulus compared with the MOVAS control cell sheets but were not significantly different from that of Acta2 hrGFP− cell sheets. The moduli of the samples were in the 50- to 250-kPa range, which is in the range of elastic moduli of bovine vascular SMC sheets previously reported by our group (Backman et al., 2017a, Rim et al., 2018); however, this range of moduli is on the lower end of reported stiffnesses for blood vessels and engineered vascular grafts (0.1–50 MPa) (Guo and Kassab, 2003, Lashkarinia et al., 2018, Wagenseil and Mecham, 2009). The Acta2 hrGFP+ cell sheets did, however, have significantly higher max stress at failure when compared with Acta2 hrGFP− cell sheets and MOVAS cell sheets.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Mouse iPSC-derived Acta2 hrGFP+ cell sheets had significantly higher elastic modulus compared with the MOVAS control cell sheets but were not significantly different from that of Acta2 hrGFP− cell sheets. The moduli of the samples were in the 50- to 250-kPa range, which is in the range of elastic moduli of bovine vascular SMC sheets previously reported by our group (Backman et al., 2017a, Rim et al., 2018); however, this range of moduli is on the lower end of reported stiffnesses for blood vessels and engineered vascular grafts (0.1–50 MPa) (Guo and Kassab, 2003, Lashkarinia et al., 2018, Wagenseil and Mecham, 2009). The Acta2 hrGFP+ cell sheets did, however, have significantly higher max stress at failure when compared with Acta2 hrGFP− cell sheets and MOVAS cell sheets.…”
Section: Resultssupporting
confidence: 58%
“…The elastic moduli of the iPSC-derived cell sheets in this study were lower than in our previously reported work (Backman et al., 2017a, Rim et al., 2018), which may be due to the lack of treatment with ascorbic acid, an additive used in previous studies. The moduli of the iPSC-derived cell sheets was also lower than the modulus of blood vessels (Guo and Kassab, 2003, Lashkarinia et al., 2018, Wagenseil and Mecham, 2009); however, blood vessels have a complex architectural structure composed of multiple aligned SMC layers oriented in different directions, while only single-layer cell sheets were tested in this study. Previous work from our group (Rim et al., 2018) explored mechanical properties of multi-layered bovine vascular SMC sheets; future work will need to focus on characterizing mechanical properties of stacked iPSC-derived cell sheets.…”
Section: Discussionmentioning
confidence: 94%
“…Most of these papers—nine, respectively—were published in cardiovascular surgical journals [ 13 , 21 , 22 , 25 , 27 30 , 43 ]. The other 21 studies were published in technical journals, for example, focusing on biomedical engineering or numerical methods in medicine [ 12 , 14 , 15 , 17 , 19 , 23 , 26 , 31 42 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Shunt anatomy was mostly represented by one aortic or shunt inlet and two or three outlets representing the RPA, LPA, and/or the descending aorta [ 14 16 , 23 , 25 27 , 31 , 42 , 44 ]. In three studies, the flow in the main PA was computed using a model with one inlet and one outlet [ 13 , 19 , 20 ]. Kong et al analyzed a model with one inlet and 274 outlets, making it the biggest PA anatomy studied [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…I believe that the use of new tools to mimic and analyze hemodynamic problems can be useful to decrease morbidity and mortality, especially in challenging cases. Recently, CFD has become a popular tool for elucidating physiopathology to prevent certain possible complications of congenital heart surgery ( 5 ). I suggest that surgeons should make an effort to optimize the results with the routine use of CFD in clinical practice.…”
mentioning
confidence: 99%